New insights into mitral valve dystrophy: a Filamin-A genotype–phenotype and outcome study. (6th September 2017) - Le Tourneau, Thierry; Le Scouarnec, Solena; Cueff, Caroline; Bernstein, Daniel; Aalberts, Jan J J; Lecointe, Simon; Mérot, Jean; Bernstein, Jonathan A; Oomen, Toon; Dina, Christian; Karakachoff, Matilde; Desal, Hubert; et al.
Abstract: Aims: Filamin-A ( FLNA ) was identified as the first gene of non-syndromic mitral valve dystrophy ( FLNA -MVD). We aimed to assess the phenotype of FLNA -MVD and its impact on prognosis. Methods and results: We investigated the disease in 246 subjects (72 mutated) from four FLNA -MVD families harbouring three different FLNA mutations. Phenotype was characterized by a comprehensive echocardiography focusing on mitral valve apparatus in comparison with control relatives. In this X-linked disease valves lesions were severe in men and moderate in women. Most men had classical features of mitral valve prolapse (MVP), but without chordal rupture. By contrast to regular MVP, mitral leaflet motion was clearly restricted in diastole and papillary muscles position was closer to mitral annulus. Valvular abnormalities were similar in the four families, in adults and young patients from early childhood suggestive of a developmental disease. In addition, mitral valve lesions worsened over time as encountered in degenerative conditions. Polyvalvular involvement was frequent in males and non-diagnostic forms frequent in females. Overall survival was moderately impaired in men ( P  = 0.011). Cardiac surgery rate (mainly valvular) was increased (33.3 ± 9.8 vs. 5.0 ± 4.9%, P  < 0.0001; hazard ratio 10.5 [95% confidence interval: 2.9–37.9]) owing mainly to a lifetime increased risk in men (76.8 ± 14.1 vs. 9.1 ± 8.7%, P  < 0.0001). Conclusion: FLNA -MVD is a developmental and degenerative disease with complex phenotypic expression which can influence patient management. FLNA -MVD has unique features with both MVP and paradoxical restricted motion in diastole, sub-valvular mitral apparatus impairment and polyvalvular lesions in males. FLNA -MVD conveys a substantial lifetime risk of valve surgery in men.